PIEZO1 loss-of-function compound heterozygous mutations in the rare congenital human disorder Prune Belly Syndrome - Nathalia G. Amado; Elena D. Nosyreva; David Thompson; Thomas J. Egeland; Osita W. Ogujiofor; Michelle Yang; Alexandria N. Fusco; Niccolo Passoni; Jeremy Mathews; Brandi Cantarel; Linda A. Baker; Ruhma Syeda (Nature Communications, 2024)
Abstract Prune belly syndrome (PBS), also known as Eagle-Barret syndrome, is a rare, multi-system congenital myopathy primarily affecting males. Phenotypically, PBS cases manifest three cardinal pathological features: urinary tract dilation with poorly contractile smooth muscle, wrinkled flaccid ventral abdominal wall with skeletal muscle deficiency, and intra-abdominal undescended testes. Genetically, PBS is poorly understood. After performing whole exome sequencing in PBS patients, we identify one compound heterozygous variant in the PIEZO1 gene. PIEZO1 is a cation-selective channel activated by various mechanical forces and widely expressed throughout the lower urinary tract. Here we conduct an extensive functional analysis of the PIEZO1 PBS variants that reveal loss-of-function characteristics in the pressure-induced normalized open probability (NPo) of the channel, while no change is observed in single-channel currents. Furthermore, Yoda1, a PIEZO1 activator, can rescue the NPo defect of the PBS mutant channels. Thus, PIEZO1 mutations may be causal for PBS and the in vitro cellular pathophysiological phenotype could be rescued by the small molecule, Yoda1. Activation of PIEZO1 might provide a promising means of treating PBS and other related bladder dysfunctional states.